Effectiveness and Safety of Antifibrotic Treatment in Pulmonary Fibrosis Associated with Rheumatoid Arthritis - Martka, Martyna Magdalena; Skorupska, Marta; Aleksiej, Andrzej; Popławska, Natalia Aleksandra; Śliz, Justyna; Czeczotka, Magdalena Joanna; Woźniak, Krzysztof (Quality in Sport, 2024)
Introduction and Objective. Rheumatoid arthritis (RA) stands as a chronic, systemic autoimmune inflammatory ailment. Lung involvement is one of the most common extra-articular manifestations of RA. Rheumatoid Arthritis-Associated Interstitial Lung Disease (RA-ILD) is a severe, progressive disease leading to pulmonary fibrosis, characterized by deterioration of lung function, exacerbation of symptoms and typical radiological features, and early mortality. Review methods and materials This review utilized PubMed, Mendeley by using search terms such as pulmonary fibrosis in rheumatoid arthritis nintedanib treatment, and pulmonary fibrosis in rheumatoid arthritis pirfenidone treatment. All searches were verified by humans, duplicated results and unreliable have been rejected. In addition, case reports and previously established literature reviews were excluded from the review. We used all available original studies evaluating and comparing the efficacy and safety of anti-fibrotic drugs to create this review. Brief description of the state of knowledge In this review, we discuss therapeutic strategies for antifibrotic treatment involving nintedanib and pirfenidone. Furthermore, we compare the efficacy of both drugs, their influence on the extension of life, their safety profiles, and associated side effects based on research findings, and discuss the molecular mechanisms of their action. Summary Clinical trials concerning RA-ILD showed that nintedanib and pirfenidone slow the rate of FVC decline in patients with RA-ILD. The safety profile observed in both drugs was similar simultaneously occurring mainly gastrointestinal symptoms. Both drugs have been approved for the RA-ILD treatment program, nevertheless in the current body of knowledge, it is not feasible to definitively determine which drug therapy should be initiated first, as their characteristics are notably similar.